2022
DOI: 10.1002/ente.202200113
|View full text |Cite
|
Sign up to set email alerts
|

Piezo/Triboelectric Effect Driven Self‐Powered Gas Sensor for Environmental Sensor Networks

Abstract: With the growing concern about the safety of the spaces where people work and live, the development of fast and accurate real‐time safety monitoring systems such as gas sensors to detect harmful gas such as H2S, NH3, and NO x is essential. For effective monitoring, a wireless sensor system that can be used anytime, anywhere is required, but there is still a limit to the power supply to operate it. Self‐powered gas sensors with piezoelectric/triboelectric nanogenerators (PENGs/TENGs) are receiving considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…A composite consisting of CeO 2 /Ce 2 O 3 /NiO x with an average crystal size of 22.4 nm was obtained by increasing microwave power to 700 W. When microwave power is increased to 900 W (d3), however, CeO 2 nanoparticles with an average crystal size of 4.9 nm are almost formed. Our previous research indicated that microwave pulses are an important parameter affecting the crystallinity and morphology of the final product 31 33 . The synthesis of catalysts was carried out under three different pulse conditions (30 s on, 60 s off, and 30 s on, 30 s off).…”
Section: Resultsmentioning
confidence: 99%
“…A composite consisting of CeO 2 /Ce 2 O 3 /NiO x with an average crystal size of 22.4 nm was obtained by increasing microwave power to 700 W. When microwave power is increased to 900 W (d3), however, CeO 2 nanoparticles with an average crystal size of 4.9 nm are almost formed. Our previous research indicated that microwave pulses are an important parameter affecting the crystallinity and morphology of the final product 31 33 . The synthesis of catalysts was carried out under three different pulse conditions (30 s on, 60 s off, and 30 s on, 30 s off).…”
Section: Resultsmentioning
confidence: 99%
“…2) As the energy harvesting system, the integration of the smart ZIB with the photo-rechargeable system (solar battery) or the friction power generation system (triboelectric nanogenerator) could realize the reversible energy storage and conversion. [198,199] The effective integration could significantly reduce the inner volume space and the weight of the wearable electronics, which is also beneficial for the utilization and portability. [197] It is also the direct strategy to achieve the collection of discontinuous resources, and provide the continuous energy supplying in the integrated system for electronic devices in future.…”
Section: The Integrated System Based On Smart Zinc Batterymentioning
confidence: 99%
“…In comparison to individual nanogenerators, this nanogenerator type can provide high and efficient power density [ 95 ]. Recent research has led to the development of hybrid nanogenerators based on piezoelectric–pyroelectric [ 96 , 97 , 98 ], triboelectric–piezoelectric [ 31 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ], electromagnetic–triboelectric [ 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ], triboelectric–piezoelectric–pyroelectric [ 133 , 134 , 135 , 136 ], triboelectric–piezoelectric–electromagnetic [ 137 , 138 , 139 , ...…”
Section: Operation Principlementioning
confidence: 99%